New record of Myotis ciliolabrum (Merriam, 1886) (Mammalia, Chiroptera) from the State of Mexico, Mexico - Noé González-Ruiz; Estefanía Nava; José Ramírez-Pulido; Diego F. García-Mendoza; Arturo Salame-Méndez; Alondra Castro-Campillo (Check List, 2024)
Myotis ciliolabrum (Merriam, 1886) is an insectivorous bat of the family Vespertilionidae and has a wide distribution from British Columbia, Alberta, and Saskatchewan in Canada, most of the western and central United States of America to central Mexico. In this study, we report one of the southernmost records from State of Mexico, based on two females collected in 1980 and stored in the Mammals Collection of the Universidad Autonóma Metropolitana. These records increases the knowledge on the distribution of this rare bat in Mexico.